Impact of metformin use on the outcomes of newly diagnosed diffuse large B‐cell lymphoma and follicular lymphoma. (28th May 2019) - Wang, Yucai; Maurer, Matthew J.; Larson, Melissa C.; Allmer, Cristine; Feldman, Andrew L.; Bennani, N. Nora; Thompson, Carrie A.; Porrata, Luis F.; Habermann, Thomas M.; Witzig, Thomas E.; Ansell, Stephen M.; Slager, Susan L.; et al.
Summary: The diabetes mellitus (DM) drug metformin targets mechanistic/mammalian target of rapamycin and inhibits lymphoma growth in vitro . We investigated whether metformin affected outcomes of newly diagnosed diffuse large B‐cell (DLBCL, n = 869) and follicular lymphoma (FL, n = 895) patients enrolled in the Mayo component of the Molecular Epidemiology Resource cohort study between 2002 and 2015. Hazard ratios (HR) and 95% confidence intervals (CIs) adjusted for age, sex, body mass index, prognostic index and treatment were used to estimate the association of metformin exposure (No DM/No metformin; DM/No metformin; DM/Metformin) with event‐free (EFS), lymphoma‐specific (LSS) and overall (OS) survival. Compared to No DM/No metformin DLBCL patients, there was no association of DM/Metformin ( n = 48; HR = 1·05, 95% CI 0·59–1·89) or DM/No metformin( n = 54; HR = 1·41, 95% CI 0·88–2·26) with EFS; results were similar for LSS and OS. Compared to No DM/No metformin FL patients, there was no association of DM/Metformin ( n = 37; HR = 1·16, 95% CI 0·71–1·89) or DM/No metformin ( n = 19; HR = 1·16, 95% CI 0·66–2·04) with EFS; results were similar for LSS. However, DM/Metformin was associated with inferior OS (HR = 2·17; 95% CI 1·19–3·95) compared to No DM/No metformin. In conclusion, we found no evidence that metformin use was associated with improved outcomes in newly diagnosed DLBCL and FL.